Accelerating Variational Quantum Eigensolver Convergence using Parameter Transfer - Skogh, Mårten; Rahm, Martin (Chalmers University of Technology, 2023)
Results of quantum computer simulations, using the Variational Quantum Eigensolver (VQE). The dataset contains data calculated using various parameters and settings. The goal of the data is to see how these parameters and settings affect the potential reduction of VQE optimization iterations.

Resultat av kvantdatorsimuleringar med hjälp av Variational Quantum Eigensolver (VQE). Datauppsättningen innehåller data som beräknats med olika parametrar och inställningar. Målet med data är att se hur dessa parametrar och inställningar påverkar den potentiella minskningen av VQE-optimeringsiterationer.
Snabbare konvergens för Variational Quantum Eigensolver genom parameteröverföring
Keywords: electronic structure; optimization; quantum computing; Atom and Molecular Physics and Optics; Atom- och molekylfysik och optik; Other Physics Topics; Annan fysik; Physical Chemistry; Fysikalisk kemi; Theoretical Chemistry; Teoretisk kemi